Penerapan Akad dan Prinsip Syaiah dalam Produk Perbankan: Studi Empiris pada PT BPRS Berkah Dana Fadhlillah Kota Pekanbaru - Helmawati Harahap; Azwar Azwar; Faras Darmawati; Desy Rahmawati; Mhd Aditya Pratama; Habib Auda Alfarizi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to examine the implementation of contracts (akad) and Sharia principles in banking products at PT BPRS Berkah Dana Fadhlillah. The rapid development of Islamic financial institutions requires alignment between theoretical concepts and their practical implementation, particularly in the use of contracts and the application of Sharia principles. However, there are still public doubts regarding the Islamic financial system, especially in distinguishing between profit margins and interest. Therefore, this study is important to determine the extent to which contracts and Sharia principles are applied in actual banking products. This research employs a qualitative method with a descriptive approach. Data were collected through interviews, observation, and documentation. The findings indicate that the implementation of contracts and Sharia principles in banking products at PT BPRS Berkah Dana Fadhlillah has been carried out in accordance with theoretical concepts. Financing products such as murabahah, ijarah, istisna’, and musyarakah are implemented using clearly defined contracts that are agreed upon at the beginning of the transaction. In addition, Sharia principles such as justice, transparency, and partnership have been applied in the bank’s operations. In conclusion, the implementation of contracts and Sharia principles at PT BPRS Berkah Dana Fadhlillah is consistent with theoretical frameworks, although challenges remain in terms of public understanding. This study is expected to contribute to the development of Islamic financial institutions and serve as a reference for future research.